Optimising agricultural food production and biodiversity in European landscapes: Report of an online-workshop - Anne Alix; Dany Bylemans; Jens Dauber; Peter Dohmen; Katja Knauer; Lorraine Maltby; Christoph J. Mayer; Zelie Pepiette; Balthasar Smith (Johann Heinrich von Thünen-Institut, 2022)
An intrinsic feature of agriculture is the alteration of biodiversity within the cultivated area in favour of the production of the crop species. Ploughing, mechanical weeding or the use of herbicides, for example, reduce plant diversity and abundance, and influence other species that rely on these plants for food or habitat. However, both food security and biodiversity are important for human health and wellbeing. The overarching question is how can negative influences of agriculture on biodiversity be reduced and positive interactions be enhanced toward an efficient and sustainable food production. That is, how can we optimise (European) landscapes for food production and biodiversity. Identifying a consensual and targeted solution to this optimisation problem requires the involvement of all relevant stakeholders in an open discussion informed by data and science. To this end a participatory workshop with a professional independent facilitator was organised under the auspices of the Society of Environmental Toxicology and Chemistry (SETAC) with participants from a range of affiliations from academia, authorities, farming, industry and Non-Governmental Organisations (NGOs). Participants were invited for their general or specific expertise and scientific knowledge and not simply to represent their institutions. To generate a truly collaborative and creative environment for discussion, significant time was allocated to trust building, articulating different perspectives, problem formulation and defining harmonised principles and criteria. The workshop was organised into four virtual workshops of half-day sessions spread between December 2020 and June 2021. Through a process of visualisation, polarity mapping and reconciliation, differing perspectives on the advantages and limitations of managing agricultural landscapes for either biodiversity or food production were collated and ways to reduce potential conflicts discussed; the emerging themes being communication, education, collaboration, integration, application and incentivisation. Codeveloped agricultural scenarios were used to successfully identify approaches that would enable maintaining efficient and sufficient food production in Europe whilst significantly improving biodiversity in agricultural landscapes. Whilst many of the approaches identified were already in place, new (combinations of) approaches and ways to improve their implementation were identified. These included tailoring solutions to local needs and conditions, incentivising farmers to adopt specific approaches and using living laboratories to demonstrate the effectiveness of combining multiple approaches at scale. The workshop proposals and recommendations, which were agreed across all stakeholders, will contribute to reducing barriers to implementation of solutions and accelerating progress towards reaching the shared goal of optimising food production and biodiversity in European agricultural landscapes.
urn:nbn:de:gbv:253-202210-dn065446-5
Keywords: 630; agriculture; biodiversity; food production; farming; land management; scenarios; co-development; tailored solutions; incentives; sustainability